2019
DOI: 10.1108/md-06-2018-0681
|View full text |Cite
|
Sign up to set email alerts
|

Whether analogue countries exhibit similar women entrepreneurial activities?

Abstract: Purpose While there are many studies on the impacts of formal institutions such as government financial supporting and tax preferential policies on women entrepreneurial entry, few attempted to explore how informal institutions causes cross-country differences in women entrepreneurship. The purpose of this paper is to investigate whether countries (Pakistan and Malaysia) with similar religious belief, political system and government policies exhibits similar level of women entrepreneurial activity from an info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…We also find that in factor-driven economies many cultural reasons may force women to engage in necessity-based entrepreneurship. These women are less educated, lack formal financing as well as fear of failure and career choices are not relevant factors for them to pursue entrepreneurship ( Junaid et al, 2019 ). In this respect, media representation of female entrepreneurs may positively influence the success of women entrepreneurs ( Ruth Eikhof, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also find that in factor-driven economies many cultural reasons may force women to engage in necessity-based entrepreneurship. These women are less educated, lack formal financing as well as fear of failure and career choices are not relevant factors for them to pursue entrepreneurship ( Junaid et al, 2019 ). In this respect, media representation of female entrepreneurs may positively influence the success of women entrepreneurs ( Ruth Eikhof, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Model 3F indicates that starting a business is socially acceptable for women if they hold the necessary skills, knowledge and experience to engage in entrepreneurial activities ( Junaid et al, 2019 ). Existing literature on women’s entrepreneurship reports that normative support of a country’s institutional environment is the most critical determinant of the emergence of women’s entrepreneurial activities ( Baughn et al, 2006 ; Yousafzai et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In developing countries, especially in South Asia, social and traditional constraints, and misunderstood religious beliefs hinder females to establish, expand, and utilize business networks. In most cases, females are required to have a male partner to sign deals and negotiate with business partners such as financers, investors, customers, and suppliers (Junaid, He, Yadav, & Asare‐Kyire, 2019). Such deep‐rooted sociocultural beliefs restrict business opportunities for women.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Thus, for men, business ties are expected to be more beneficial than for women. The literature has also noted that, females face more difficulties than males do in getting assistance from government departments (Agarwal, 1994; Della‐Giusta & Phillips, 2006; Junaid et al, 2019), because government employees (predominantly males) try to reinforce negative social attitudes that favor males than females, who are more obedient, reliant, self‐sacrificing, relationship oriented, and have limited information. A recent study by Venkatesh, Shaw, Sykes, Wamba, and Macharia (2017) has indicated that ties with community increases women's entrepreneurial activities, while ties with government officials decreases their entrepreneurial activities.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%